An Integrated Environmental Assessment of MSW Management in a Large City of a Developing Country: Taking the First Steps Towards a Circular Economy Model - Lara-Topete, Gary Ossmar; Yebra-Montes, Carlos; Orozco-Nunnelly, Danielle A.; Robles-Rodríguez, Carlos Eduardo; Gradilla-Hernández, Misael Sebastián (Frontiers in Environmental Science, 2022)
The Guadalajara Metropolitan Area (GMA), the third most populous city in Mexico, currently faces the closure of its main sanitary landfill. In this study, environmental life cycle assessment was used to evaluate the environmental performance, global warming impact and the abiotic resources depletion of the current MSW management model and two potential scenarios for the improvement of MSW management in a GMA subsystem,, which currently disposes of their MSW at the closing sanitary landfill. The two potential scenarios include a mechanical treatment plant and a mechanical biological treatment plant. The results indicate that the current MSW management system (baseline) contributes 111.21 Gg CO2-eq/year to Jalisco State’s GHG emissions, while the two potential scenarios displayed a net reduction of 24 and 34% of CO2-eq emissions, respectively, due to the avoided emissions resulting from the recovery of valuable materials and the potential partial substitution of petroleum coke by refuse-derived fuel in cement kilns, despite the increase in energy demand derived from the implementation of the treatment plants. Regarding the abiotic resource depletion, the rates of material recovery in the current scenario produce a reduction of 0.16 Gg Sb-eq/year, which constitutes a minimal fraction compared to the potential reduction in fossil fuels when considering the avoided coke extraction, which provides a reduction of 5.62 Gg Sb-eq/year. The sensitivity analysis revealed that some key parameters, such as the fraction of food and kitchen and plastic waste in the MSW, can alter the ranking order of scenarios. Finally, the sociocultural, geopolitical, technological/infrastructural, and economic challenges for the implementation of the potential scenarios were identified through a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. Recycling of the recovered materials and treatment of the organic fraction were found to be key strategies to reduce GHG emissions and the abiotic resource depletion in developing countries. Furthermore, the formalization of waste pickers’ (WP) activities, the regularization of sanitary landfills conditions and operation, and the enhancement of source separation and selective collection must be addressed prior to the introduction of the treatment technologies.